2023
DOI: 10.3390/pharmaceutics15020338
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Physico-Chemical, Antimicrobial and Angiogenic Properties of Graphene-Oxide/Cellulose Nanocomposites for Wound Healing

Abstract: Graphene oxide (GO) and its reduced form (rGO) have recently attracted a fascinating interest due to their physico-chemical properties, which have opened up new and interesting opportunities in a wide range of biomedical applications, such as wound healing. It is worth noting that GO and rGO may offer a convenient access to its ready dispersion within various polymeric matrices (such as cellulose and its derivative forms), owing to their large surface area, based on a carbon skeleton with many functional group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 148 publications
0
5
0
Order By: Relevance
“…The Role of Drugs, Cells, and miRNA Loaded into GO-Based Nanomaterials GO-based nanocomposites are promising carriers for drugs, stem cells, microRNAs, and other therapeutic agents (Table 2). These nanocomposites can be employed in the treatment of various diseases and play a significant role in tumor inhibition, angiogenesis, bacterial growth inhibition, and tissue repair [74][75][76]. Therapeutic agents, such as bisphosphonates, parathyroid hormone, strontium, BMSCs, and microRNAs, can be utilized to balance the functions of osteoclasts and osteoblasts, shifting from overactive bone resorption to normal bone metabolism, thus improving the microenvironment of osteoporotic fractures [77].…”
Section: Enhancing the Treatment Of Osteoporotic Fracturesmentioning
confidence: 99%
“…The Role of Drugs, Cells, and miRNA Loaded into GO-Based Nanomaterials GO-based nanocomposites are promising carriers for drugs, stem cells, microRNAs, and other therapeutic agents (Table 2). These nanocomposites can be employed in the treatment of various diseases and play a significant role in tumor inhibition, angiogenesis, bacterial growth inhibition, and tissue repair [74][75][76]. Therapeutic agents, such as bisphosphonates, parathyroid hormone, strontium, BMSCs, and microRNAs, can be utilized to balance the functions of osteoclasts and osteoblasts, shifting from overactive bone resorption to normal bone metabolism, thus improving the microenvironment of osteoporotic fractures [77].…”
Section: Enhancing the Treatment Of Osteoporotic Fracturesmentioning
confidence: 99%
“…leads to the restoration of the material, effectively repairing the damage. [205][206][207] Feng and Wang (2022) successfully demonstrated the facile preparation of chitosan-graphene oxide (CSGO) hydrogels with injectability, self-healing, and adhesive properties, enabled by a series of noncovalent bonds. Through a detailed investigation into the gelation mechanism, it was found that the intercalation of chitosan (CS) chains between GO sheets led to weakened hydrogen bonds among CS chains.…”
Section: Extrinsic Self-healingmentioning
confidence: 99%
“…Its mechanism involves various steps starting from the formation of oxygen vacancies, that is, when GO is exposed to stress or damage, oxygen atoms may be removed from the surface of the material, resulting in the formation of oxygen vacancies. This triggers a self‐healing reaction, which involves the migration of oxygen atoms from the neighboring areas to the damaged region, which leads to the restoration of the material, effectively repairing the damage 205–207 …”
Section: Recently Used Self‐healing Materials In Wound Therapymentioning
confidence: 99%
“…However, the effectiveness is particularly pronounced against Gram-positive bacteria ( Xie et al, 2020 ). Apart from the substantial inhibition observed against S. aureus and S. agalactiae , biomaterials utilizing graphene quantum dots exhibited bactericidal properties against methicillin-resistant E. coli and P. aeruginosa ( D’Amora et al, 2023 ).…”
Section: Metal/metal-oxide Nanocompositesmentioning
confidence: 99%